Influence of polysaccharides on wine protein aggregation. (1st June 2016) - Jaeckels, Nadine; Meier, Miriam; Dietrich, Helmut; Will, Frank; Decker, Heinz; Fronk, Petra
Highlights: Different protein aggregation behaviour under conditions close to reality. Importance to use model systems close to reality to investigate haze formation. Arabinogalactan leads to enhanced aggregation in a wine environment. Protein stability is generated using pectin components in buffer but not in wine. Potential haze-protective polysaccharides could not reduce protein haze. Abstract: Polysaccharides are the major high-molecular weight components of wines. In contrast, proteins occur only in small amounts in wine, but contribute to haze formation. The detailed mechanism of aggregation of these proteins, especially in combination with other wine components, remains unclear. This study demonstrates the different aggregation behavior between a buffer and a model wine system by dynamic light scattering. Arabinogalactan-protein, for example, shows an increased aggregation in the model wine system, while in the buffer system a reducing effect is observed. Thus, we could show the importance to examine the behavior of wine additives under conditions close to reality, instead of simpler buffer systems. Additional experiments on melting points of wine proteins reveal that only some isoforms of thaumatin-like proteins and chitinases are involved in haze formation. We can confirm interactions between polysaccharides and proteins, but none of these polysaccharides is able to prevent haze in wine.